Impact of farmer field schools on soil and crop management among smallholders in North Rift, Kenya - D.K Bunyatta; C.A Onyango; J.K Kibett (Journal of Agricultural Extension Management, 2015)
The Farmer Field School (FFS) approach has been tried widely and has created a positive impact on crop and soil productivity in many Asian and African countries. Kenya Agricultural Research Institute (KARI) introduced FFS approach in the year 2001 as an alternative to the conventional approach to promote dissemination of Soil and Crop Management Technologies. The purpose of this study was to determine the impact of the Soil and Crop Management Technologies (S&CMTs) disseminated through Farmer Field Schools (FFSs) on the Farming Systems and farm productivity among the smallholder farmers in North Rift, Kenya. Eight technologies were scaled-out using the approach and the conventional extension methods. A survey methodology with an Ex-post facto research design was used with a sampling frame consisting of 6,560 small-scale farmers. A sample of 180 FFS and 180 Non-FFS farmers was chosen for the study, using proportionate stratified random sampling. Data was collected through interview schedules administered to FFS and Non FFS farmers. The results indicated that there were significant differences (P<0.05) in knowledge acquired in S&CMTs and impact of S&CMTs on farming system and productivity between FFS and nonFFS panicipants. It was concluded that farmers who were exposed to the FFS training methodology had a better understanding, adoption, practice and higher impact of S&CMTs as compared to the non-FFS farmers. The main recommendation from this study was therefore, the need to scale-up and scaling out the S&CMTs using the FFS approach in counties in the Nonh Rift region of Kenya. ><0.05) in knowledge acquired in S&CMTs and impact of S&CMTs on farming system and productivity between FFS and non FFS participants. It was concluded that farmers who were exposed to the FFS training methodology had a better understanding, adoption, practice and higher impact of S&CMTs as compared to the non-FFS farmers. The main recommendation from this study was therefore, the need to scale-up and scaling out the S&CMTs using the FFS approach in counties in the North Rift region of Kenya